Comparative Analysis of Czech Accounting with International Regulation from SMEs Perspective - Jiří Strouhal; Marie Paseková; Libuše Müllerová (European Financial and Accounting Journal, 2011)
Use of harmonized accounting standards may reduce investor's uncertainty and can thus reduce the cost of capital. It can significantly improve the communication between business users and all their statements. Due to the globalization of business and international harmonization of financial reporting Czech Republic experiences a shift in paradigms from historical costs accounting towards fair value measurement. Paper provides an analysis between national accounting legislature and international referential. There is also provided how the ability to measure accounting harmonization can be helpful from the perspective of a globalized world. A comparative analysis between Czech accounting regulation and IFRS or IFRS for SMEs show the level of compatibility between these three sets of accounting regulation.
Keywords: 650; International harmonization; Globalization; IFRS; Econometric tools; Czech Republic